(untitled) (Orfeu, 2025)
The general aim of this research was to investigate the professional insertion of graduates of degree programmes in music education, offered by public higher education institutions of the state of Parana, Brazil, graduated from 2009 to 2014, under graduate degree of each programme. The method chosen to carry out this research was the survey, which has been answered by a sample of 215 graduates. The results of professional insertion indicate precocity in the graduates’ professional insertion, which, in most cases, begins even before entering the higher education programmes, in activities of music teaching, other activities in the field of music, and, even, activities in areas not related to music. The practice of multiple activities is kept, even though music teaching practice is predominant, indicating that the degree courses in music education are fulfilling their main purpose of teachers training.